Interior of Steinbeck's Sag Harbor Writing Room - Jackson Benson:::Creator::::::::::::
A picture from inside Geoyous Garde, Steinbeck's hexangonal writing room, which looked out over cove near Bluff Point in Sag Harbor, New York. The table was an adjustable drafting table. Negative and digital copy only. No hard copy.